Psychological maladaptation of people with overeating - Sinkevych, Inna (Psychosomatic Medicine and General Practice, 2022)
Overeating is a new diagnosis in the fifth edition of the Manual of Diagnosis and Statistics of Mental Disorders (DSM-5) and the eleventh revision of the International Classification of Diseases (ICD-11). The prevalence of compulsive overeating is much higher than anorexia nervosa, bulimia nervosa and other eating disorders. Overeating is characterized by recurrent episodes of overeating without compensatory behavior, such as vomiting or excessive exercise to prevent weight gain. Episodes of overeating are accompanied by feelings of loss of control, anxiety, depression or guilt, overeating is associated with severe psychological and emotional disorders, which hinders the ability to self-regulation. Several factors can affect eating behavior and stimulate food intake beyond needs. For many people, eating is used as a means to manage negative emotions. Overeating can be seen as an maladaptive way of overcoming negative emotions.